Sustainable planning in Wuhan City during COVID-19: an analysis of influential factors, risk profiles, and clustered patterns - Zhou, Peng; Zhang, Hailu; Liu, Lanjun; Pan, Yue; Liu, Yating; Sang, Xuanhao; Liu, Chaoqun; Chen, Zixuan (Frontiers in Public Health, 2023)
The outbreak of novel coronavirus pneumonia (COVID-19) is closely related to the intra-urban environment. It is important to understand the influence mechanism and risk characteristics of urban environment on infectious diseases from the perspective of urban environment composition. In this study, we used python to collect Sina Weibo help data as well as urban multivariate big data, and The random forest model was used to measure the contribution of each influential factor within to the COVID-19 outbreak. A comprehensive risk evaluation system from the perspective of urban environment was constructed, and the entropy weighting method was used to produce the weights of various types of risks, generate the specific values of the four types of risks, and obtain the four levels of comprehensive risk zones through the K-MEANS clustering of Wuhan's central urban area for zoning planning. Based on the results, we found: ①the five most significant indicators contributing to the risk of the Wuhan COVID-19 outbreak were Road